OPTIMALISASI PENGETAHUAN MENARCHE GUNA MENYIKAPI PERIODE MENARCHE PADA REMAJA PUTRI DI KOTA STABAT: Menarche; Menstruate; Personal Hygiene - Ria Julita Sari (Universitas Prima Indonesia, 2020)
The problems currently, lack of knowledge about her period while it is very required by a teenage girl, physical problems that might arise from that knowledge is a lack of personal hygine so it can run the risk of infection in the urinary tract ( isk ).According to fishben and azjen, knowledge someone about a thing would affect his attitude.The gesture can be positive or negative depends on individual understanding about something that, so with knowledge of good kids really can understand what is happening to him and know how to act.Adolescent girls need information about the process of menstruation and health during menstruation and will have trouble as excessive anxiety face menstrual first if earlier he had never gain knowledge of menstruation.When menarche confused feelings, nervous and uncomfortable always cover the feelings one woman who undergo menstruation for thefirst time ( menarche ), your first period or menarche is a natural thing that must be experienced by every woman normal and do not need.The purpose of this research is to optimize its knowledge in order to addressing the period of menarche on teenage daughter in the city stabat.This research to explain the relationship menarche knowledge and attitudes face menarche for teenage princess stabat, langkat. districtA method of this study using several phases in data collection and data analysis.For data collection, there are 3 stages yaitu (a) editing (b) coding dan (c) tabulating.